2011
DOI: 10.1108/10650741111181599
|View full text |Cite
|
Sign up to set email alerts
|

The Socratic dialogue in asynchronous online discussions: is constructivism redundant?

Abstract: Purpose -This paper aims to examine Socratic dialogue in asynchronous online discussions in relation to constructivism. The links between theory and practice in teaching are to be discussed whilst tracing the origins of Socratic dialogue and recent trends and use of seminar in research based institutions. Design/methodology/approach -Many online degree courses employ asynchronous discussions where the teacher, acting as a moderator, is seen as the guide on the side rather than the sage on the stage. Such an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Previous studies have focused on varied factors of undergraduate physics students' learning and/or approaches: for example, teacher-related epistemological factors (Karatas & Erden, 2017;Kingsley, 2011;Stathopoulou & Vosniadou, 2007), students' and experts' metacognition (Gašević et al, 2015;Jonassen et al, 2003), students' epistemological beliefs (Elby, 2001;Fletcher & Luft, 2011), students' attitudes and beliefs about learning physics and the structure of physics knowledge (Erdemir & Bakırcı, 2009;Guido, 2018;Shin et al, 2003), students' expectations of physics teaching (Marshall & Linder, 2005) and students' difficulties/inabilities/misunderstanding of problem-solving strategies (Gök, 2011;Gök & Sılay, 2009;Pol et al, 2005). Further, some studies, which have challenged students' problem-solving skills, have suggested student-centered instructional practices for problem-solving (Ali, 2019;Saka, 2011;Çalıskan & Selç uk, 2010;Gök, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have focused on varied factors of undergraduate physics students' learning and/or approaches: for example, teacher-related epistemological factors (Karatas & Erden, 2017;Kingsley, 2011;Stathopoulou & Vosniadou, 2007), students' and experts' metacognition (Gašević et al, 2015;Jonassen et al, 2003), students' epistemological beliefs (Elby, 2001;Fletcher & Luft, 2011), students' attitudes and beliefs about learning physics and the structure of physics knowledge (Erdemir & Bakırcı, 2009;Guido, 2018;Shin et al, 2003), students' expectations of physics teaching (Marshall & Linder, 2005) and students' difficulties/inabilities/misunderstanding of problem-solving strategies (Gök, 2011;Gök & Sılay, 2009;Pol et al, 2005). Further, some studies, which have challenged students' problem-solving skills, have suggested student-centered instructional practices for problem-solving (Ali, 2019;Saka, 2011;Çalıskan & Selç uk, 2010;Gök, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the article is examined, we have observed that many studies have been conducted on physics pre-service teachers and on the solution of physics problems. We have seen that studies on the learning approaches of physics pre-service teachers are generally carried out by taking into account the focal points such as epistemological factors-beliefs (Elby, 2001;Fletcher & Luft, 2011;Karatas & Erden, 2017;Kingsley, 2011;Stathopoulou & Vosniadou, 2007), metacognition (Gašević et al, 2015;Jonassen et al, 2003), attitude towards physics learning (Erdemir & Bakırcı, 2009;Guido, 2018;Shin et al, 2003), expectations from physics teaching (Marshall & Linder, 2005) and problem solving strategies (Gök, 2011;Gök & Sılay, 2009;Pol et al, 2005).However, when the studies on the solution of physics problems are examined, we have observed that these studies are generally carried out by taking into consideration the fundamentals such as achievement (Ghavami, 2003;Taşoğlu, 2009), beliefs (Mistades, 2007), attitudes (Balta et al, 2016;Erdemir, 2009;Good et al, 2019), conceptual understanding (Ergün, 2010), teaching strategies (Good et al, 2019;Gök, 2012), learning (Şahin & Yörek, 2009) and evaluation (Docktor et al, 2015;Gök, 2014). In addition, we have seen that there are studies based on difficulties in problem solving (Ogünleye, 2009), problem solving understand-ings and practices (Asikainen & Hirvonen, 2010;Freitas et al, 2004), views on physics teaching approaches (Mulhall, 2005), and the differences between expert and novice problem solvers (Kohl & Finkelstein, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(p. 516-517). According to Kingsley (2011), asynchronous online discussion is one of the most valuable formats of the Socratic dialog. This format has multiple benefits including, but are not limited to, allowing learners to reflect and ongoing research before responding and allowing multiple learners to reply simultaneously.…”
Section: Questioningmentioning
confidence: 99%